Sistem Pemesanan Kopi Keliling Berbasis Website - Kevin; Dewayani, Ery (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
Increasingly rapid of technology in development encourages various business sectors to utilize technology to compete in carrying out their business. Therefore, almost every business sector currently utilizes technology, both website and mobile based. Due to the problems that arise in door-to-door coffee sales, such as permanent places that are difficult to find, technology is used to facilitate these sales. Through the existing website to support door-to-door coffee orders, sellers can easily get orders and can directly deliver the coffee to the customer. The website development uses HTML, CSS, JavaScript, and PHP programming languages and the phpMyAdmin as database. This website-based door-to-door coffee ordering information system was designed using an object-oriented analysis and design (OOAD) process.